Lanthanide doped dual-mode nanophosphor as a spectral converter for promising next generation solar cells - Singh A.K.; Singh S.K.; Kumar P.; Gupta B.K.; Prakash R.; Rai S.B. (My University, 2025)
Herein, we have successfully synthesized a lanthanide based dual-mode nanophosphor (Y0.975Yb0.020 Ho0.005VO4), capable to emit both by down-shifting and upconversion processes, via facile combustion method. The dual-mode emission in phosphor materials is still an unexplored area. The present work covers the study of structure, surface morphology, luminescent behavior and decay profile of the synthesized nanophosphor. The nanophosphor exhibits strong green emission (corresponding to 5F4, 5S2 → 5I8 transition of Ho3+ ion) on UV excitation (λex = 318 nm), via an excited state energy transfer from the charge transfer band of [VO4]3- to 5F4 state of Ho3+ ions. On the other hand, an efficient red emission of Ho3+ (5F5 → 5I8) is obtained upon infrared excitation (λex = 976 nm). We propose that the dual-mode nanophosphor could be an exceptional prospect to incorporate in next generation solar cell applications. © 2014 by American Scientific Publishers.